Elementer til en teori om den destituerende magt - Agamben, Giorgio; Bojesen, Rasmus L. (Slagmark - Tidsskrift for idéhistorie, 2015)
This essay by Giorgio Agamben is based on a lecture given in central France in the summer of 2013. Responding directly to recent occupations and insurrections – from Cairo and Istanbul to London and New York City – Agamben builds upon his existing work in order to develop and clarify his understanding of the political, and in particular, the notion of destituent power (potenza destituente). In contrast to attempts to affirm a constituent power independent of a relation to constituted power, which for Agamben both reproduce the governmental structure of the exception and represent the apex of metaphysics, destituent power outlines a force that, in its very elaboration, deactivates the governmental machine. For Agamben, it is in the sensible elaboration of the belonging together of life and form, being and action, beyond all relation, that the impasse of the present will be overcome. Ultimately, Agamben points not only towards what it means to be ungovernable, but the potential of staying so.